Autophagy contributes to regulate the ROS levels and PCD progress in TMV-infected tomatoes. (April 2018) - Zhou, Shumin; Hong, Qiang; Li, Yang; Li, Qi; Wang, Mao
Highlights: TMV localized infection on leaves can induce ROS generation in tomato root-tip cells. ● ROS accumulation in cell wall induces PCD for resistanting TMV spread. ROS accumulation in cell wall induces PCD for resistanting TMV spread. Autophagy plays an important role in regulating ROS based disease resistance and maintaining cell survival. Abstract: Programmed cell death (PCD) and autophagy are both important means for plants to resist pathogen. It is also the main biological reaction of plant immunity. In previous studies, we found that TMV local-infection on tomato leaves not only caused the PCD process in the distal root tissues, but also induced autophagy in root-tip cells. However, the reasons for these biological phenomena are unclear. In order to get deeper insight, the role of a putative inducible factor reactive oxidative species (ROS) was investigated. The situ staining and subcellular localization analysis showed that the ROS level in the root tissue of TMV infected plants was significantly promoted. TEM observation showed that the intracellular ROS was excreted into the cell wall and intercellular layer. At the same time, the results of western blot and qRT-PCR showed that the expression of autophagy related protein Atg8 and genes ( Atg5, Atg7 and Atg10 ) were increased. However, in the subsequent DPI inhibition experiments we found that the accumulation of ROS in infected plant root-tip tissues was inhibited and the autophagy in the root-tip cells also decreased. When 3-methyladenine (3-MA) was used to inhibit autophagy, there was no significant change in the ROS level in the apical tissue, while the systemic PCD process of the root-tip cells was elevated. Taken together, these results indicate that local TMV inoculation on the leaves induced the root-tip cells producing and releasing a lot of ROS into the extracellular matrix for defense against pathogen invasion. Meanwhile, ROS acted as a signaling substance and triggered autophagy in root-tip cells, in order to eliminate excessive intracellular ROS oxidative damage and maintain cell survival.